2011
DOI: 10.1007/s12170-011-0181-5
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Consumption, Blood Pressure, and Risk of Hypertension: An Evidence-Based Review of Recent Literature

Abstract: Hypertension is a major risk factor for development of stroke, coronary heart disease, heart failure, and end-stage renal disease. In a systematic review of the evidence published from 2004 to 2009, the 2010 Dietary Guidelines Advisory Committee (DGAC) concluded there was moderate evidence of an inverse relationship between the intake of milk and milk products (dairy) and blood pressure. This review synthesizes results from studies published over the past year on the relationship between dairy intake, blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 48 publications
(49 reference statements)
1
74
0
2
Order By: Relevance
“…Another mechanism in which dairy products may reduce blood pressure is through milk proteins (4). Bioactive lactotripeptides are hypothesized to lower blood pressure by inhibition of angiotensin-converting enzyme and opioid-like activities (4,27). A reciprocal relation between dairy intake and healthier dietary pattern has been shown in our study as well as in other studies (6,7,10) and suggests that the association between dairy intake and risk of hypertension could be confounded by generally healthier lifestyle and eating habits.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Another mechanism in which dairy products may reduce blood pressure is through milk proteins (4). Bioactive lactotripeptides are hypothesized to lower blood pressure by inhibition of angiotensin-converting enzyme and opioid-like activities (4,27). A reciprocal relation between dairy intake and healthier dietary pattern has been shown in our study as well as in other studies (6,7,10) and suggests that the association between dairy intake and risk of hypertension could be confounded by generally healthier lifestyle and eating habits.…”
Section: Discussionsupporting
confidence: 77%
“…Milk is a good dietary source for potassium, magnesium (25), phosphorus (4), and vitamin D (26), all of which have been proposed to have possible blood pressure-lowering potential …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that the intake of dairy products protects against cardiometabolic risk or several of its risk factors [1], [7] and [8]. Evidence, mostly in adults, has indicated that increased dairy intake may decrease the risk of high blood pressure (BP) [8] and [9], central obesity [10] and [11], and hyperinsulinemia [12]. It has been established that such dairy components as calcium, medium-chain fatty acids, and bioactive peptides may play an important role in the prevention of cardiometabolic risk and its complications via the exertion of mechanisms that include the satiety response and the regulation of insulinemia levels and BP [13].…”
Section: Introductionmentioning
confidence: 99%